The Evaluation of Incentive-Disincentive System in Tourism Development: A Case Study of Lake Linow Development, Tomohon, North Sulawesi - Boka, Ronald Yusak (Journal of Indonesian Tourism and Development Studies, 2016)
The aim of the research is to evaluate the implementation of incentive-disincentive system which area implemented in Lake Linow in term of tourism development. This result confirm that there gaps between incentive and disincentive system. Based on the calculation, it is clear that the highest satisfaction index was fond about direct funding support. Direct funding support policy is become the most preferred form of incentive systems. The second satisfaction was physical development. The highest problems and gaps related tourism development related to the social service. Stakeholder argues that social service of tourism planning and implementation facing problems, including service in legal permission in administration aspect to program implementation in the field. The development of tourism in Lake Linow potentially affects land use changes and therefore tourism development should be managed properly. The incentive-disincentive system is one of the instruments to maintain natural resources use in sustainable manner. Keywords: Lake Ecosystem, Land Uses Changes, Sustainable Tourism, Tourism Satisfaction.